Mechanical and physicochemical properties of ferro-siliceous concrete subjected to elevated temperatures. (30th September 2016) - Chu, Hong-yan; Jiang, Jin-yang; Sun, Wei; Zhang, Mingzhong
Graphical abstract: Highlights: The critical temperature range of FSCs was 400–600 °C. The relationship between compressive strength and UPV was Weibull distribution. An exponential relationship between splitting tensile strength and UPV was observed. Compared to unheated FSC, the porosity value was more than trebled after exposure to 1000 °C. Svyatoslavite that was a new crystalline phase was observed at 1000 °C. Abstract: Ferro-siliceous concrete (FSC), as a sacrificial material, is used in European Pressurized Water Reactor. This paper presents an experimental investigation on the performance of FSC with and without polypropylene (PP) fibers subjected to elevated temperatures. Mechanical and physicochemical properties of FSCs were studied at both ambient and high temperatures. The occurrence of spalling, compressive strength, splitting tensile strength, mass loss, porosity, chemical composition, crystalline phase, and thermal analysis of FSCs before and after exposure to various temperatures (200, 400, 600, 800, and 1000 °C) were comprehensively investigated. Ultrasonic pulse velocity (UPV) propagation in FSCs at different temperatures was determined by ultrasonic testing technique, and the relationships between strengths and UPV of FSCs were eventually obtained. The results indicated that, (1) the critical temperature range of FSCs was 400–600 °C; (2) the compressive strength-UPV and splitting tensile strength-UPV relationships were Weibull distribution and exponential form, respectively; (3) compared to unheated FSCs, the porosity values were more than trebled after exposure to 1000 °C.